Pendekatan Metode Lean Startup dalam Menganalisa Kepuasan Pelanggan pada Menu Masakan “Rajanya Seafood” - Sri Rahayu; Tata Sutabri (Uranus: Jurnal Ilmiah Teknik Elektro, Sains dan Informatika, 2024)
This study aims to evaluate customer satisfaction with the menu offerings at "Rajanya Seafood" using the Lean Startup approach. This method was chosen because it enables businesses to develop products that better meet customer needs and preferences through rapid experimentation cycles, continuous feedback, and regular updates. Research data was collected through direct surveys of "Rajanya Seafood" customers, focusing on aspects such as taste quality, menu variety, pricing, and service. The collected data was analyzed to identify areas needing improvement as well as potential innovations to enhance customer satisfaction. The study results indicate that the Lean Startup approach is effective in quickly understanding and responding to customer needs, thus contributing to increased customer loyalty and satisfaction. These findings are expected to serve as a reference for "Rajanya Seafood" and other culinary businesses in applying the Lean Startup strategy to achieve optimal customer satisfaction levels.